2006
DOI: 10.1002/yea.1382
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increased yeast alcohol acetyltransferase and esterase activity on the flavour profiles of wine and distillates

Abstract: The fruity odours of wine are largely derived from the synthesis of esters and higher alcohols during yeast fermentation. The ATF1-and ATF2-encoded alcohol acetyltransferases of S. cerevisiae are responsible for the synthesis of ethyl acetate and isoamyl acetate esters, while the EHT1-encoded ethanol hexanoyl transferase is responsible for synthesizing ethyl caproate. However, esters such as these might be degraded by the IAH1-encoded esterase. The objectives of this study were: (a) to overexpress the genes en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
176
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(188 citation statements)
references
References 45 publications
7
176
1
4
Order By: Relevance
“…The results showed that ATF2 overexpression significantly improved the acetate ester content of Chinese yellow rice wine. In the same manner, the expression level of ATF2 in the current study was expected to be an important limiting factor for ester synthesis in S. cerevisiae, confirming the results of Lilly et al (2006) and Verstrepen et al (2003b). These observations can inform the development of new production strategies and new yeast strains, allowing further optimization of rice wine flavor profiles in order to satisfy different sensory preferences of consumers, as well as contribute to a better understanding of the physiological role of acetate ester synthesis.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results showed that ATF2 overexpression significantly improved the acetate ester content of Chinese yellow rice wine. In the same manner, the expression level of ATF2 in the current study was expected to be an important limiting factor for ester synthesis in S. cerevisiae, confirming the results of Lilly et al (2006) and Verstrepen et al (2003b). These observations can inform the development of new production strategies and new yeast strains, allowing further optimization of rice wine flavor profiles in order to satisfy different sensory preferences of consumers, as well as contribute to a better understanding of the physiological role of acetate ester synthesis.…”
Section: Discussionsupporting
confidence: 86%
“…In 1962, Nordström demonstrated that esters are formed via an intracellular process catalyzed by alcohol acetyltransferase from acetyl coenzyme A and the corresponding alcohols. There are 3 types of AATase, namely, AATases, AATase I, and AATase II, which are encoded by ATF1, Lg-ATF1, and ATF2, respectively (Lilly et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on ester production by yeast have found that modifying parameters, such as components of the culture media and aeration conditions, have increased aroma production by three times (Etschmann. 2004;Lilly. 2006;Medeiros.…”
Section: Resultsmentioning
confidence: 99%
“…2010;Garde-Cerdán 2008). For example, the ester hydrolase activity in P. heedii CECT 11452 was 28 times higher than in P. anomala CECT 10590, while the alcohol acetyltransferase activity was 17 times higher in P. heedii CECT 11452 than in P. anomala CECT 10590 (Lilly 2006;Bisson 2010). Peddie (1990) reported that ester synthesis was very slow at the beginning of fermentation in liquid cultures of S. cerevisiae.…”
Section: Resultsmentioning
confidence: 99%